A Genomic Approach to Study Apomixis using Eragrostis curvula as a Model Species - Carballo, José (2018)
Apomixis is defined as asexual reproduction by seeds, avoiding meiotic reduction and fertilization, being generally present in polyploid plant species. Eragrostis curvula is a perennial grass native to Southern Africa. This species can be taken as a model for the discovery of genes that govern pseudogamous diplosporic apomixis since its polyploid cytotypes (4x to 8x) may undergo sexual reproduction, facultative apomixis, or obligate apomixis whereas diploids are always sexual. Here we present the first draft of a diploid version of the E. curvula genome. The cultivar selected was Victoria (~1200 Mb) originated from in vitro culture of inflorescences of the apomictic cv. Tanganyika (2n=4x=40). Two libraries were prepared with fragment lengths of 20 kb and 10 kb to get longer reads and to increase the coverage, respectively. The sequencing through PACBIO technology resulted in 6.223.627 and 3.309.811 reads respectively with 90X coverage. The assembly was performed using the software Falcon. The N50 was 380.026 bp with 3.118 contigs representing 95% of the haplotype length. The software BUSCO was used to find single copy orthologous genes, being represented 97% of the BUSCO genes. Dovetail Hi-rise software revealed the architecture of the complete genome chromosome-by-chromosome. The first draft of E. curvula genome showed high level of contiguity with a coverage of 95% of the diploid genome. The high proportion of annotated genes would allow the identification of those related to the reproductive mode. This draft represents the start point to obtain more complex tetraploid genomes, harboring the region/s involved in apomixis.